Lake Hazar basin: A negative flower structure on the east anatolian fault system (EAFS), SE Turkey - Aksoy, Ercan; Inceoez, Murat; Kocyigit, Ali (Tubitak Scientific & Technological Research Council Turkey, 2007)
The East Anatolian Fault System ( EAFS) is a 30-km-wide, 700-km-long and NE-trending sinistral strike-slip megashear belt between the Anatolian platelet in the northwest and African-Arabian plates in the southeast. It is located between Karliova County in the NE and Karatas ( Adana)-Samandag ( Antakya) in the SW. In the Lake Hazar region, the EAFS consists of five fault zones. These are, from north to south, the Elazig fault zone, the Uluova fault zone, the Sivrice fault zone, the Adiyaman fault zone and the Lice-Cermik fault zone; in previous studies only the Sivrice fault zone has been reported to be part of the EAFS. The 2-4-km-wide and 180-km-long Sivrice fault zone contains the master fault of the system. It bifurcates into several sub-fault zones and isolated faults resulting in a 5-km-wide, 32-km-long, active lensoidal depression bounded by a series of short to long and curved fault segments with considerable amounts of normal-slip component, particularly on the southern margin. This strike-slip depression was previously reported and interpreted to be a classical pull-apart basin or rhombgraben basin originating from a left step-over located in the northeastern corner of Lake Hazar. In contrast to this earlier interpretation, our detailed field geological mapping of active faults indicates that there is no any left stepover at the northeast corner of Lake Hazar. In lieu of this, the master fault of the EAFS bifurcates into two substrands nearby Kartaldere village in the east which then run in a SW direction across Lake Hazar resulting in two sub-parallel lensoidal depressions separated by an intervening horst. This strike-slip geometry is here termed a negative flower structure. This interpretation is supported by basin-ward curved boundary faults with considerable normal-slip component of movement and by the bathymetry of Lake Hazar. Back-tilted fault blocks, uplifted and dissected Plio-Quaternary terrace conglomerates, fan-delta deposits and associated syn-sedimentary structures indicate that neotectonic infill of the basin has accumulated under the influence of a strike-slip tectonic regime. The left-lateral strike-slip amount and the vertical throw amount accumulated along the Sivrice fault zone are 9 +/- 1 km and 1317 +/- 10 m, respectively. These values yield strike- and vertical-slip rates of 4 mm/yr and 0.5 mm/yr, respectively, along the Sivrice fault zone. However, the slip rates along the EAFS must be greater because the EAFS around Lake Hazar consists of five fault zones which all share the slip rate.
Keywords: East Anatolian fault system; lake Hazar basin; negative flower structure; Turkey